Bi‐Stable Metamaterials with Intrinsic Memory for Selective Wave Filtering Based on Frequency and Amplitude - Nathan N. Stenseng; Mahmoud M. Samak; Osama R. Bilal (Advanced Science)
Abstract Analytical, numerical, and experimental methods are used to investigate the utility of metamaterials in controlling harmonic waves based on both their amplitude and frequency. By programming the metamaterials to support bi‐stable configurations (i.e., two stable phases), the required conditions are elucidated for a transition wave (i.e., a topological soliton) to nucleate due to harmonic excitation, causing a phase change within our metamaterial. As each of these phases has its own unique transmission frequency range, such phase change is harnessed to control harmonic waves based on both their amplitude and frequency. As a demonstration of principle, a low/high‐pass filter is shown by tuning the same metamaterial to change phase; from transmission to attenuation and vice versa. In addition, phase transitions taking place while preserving the metamaterial's state of attenuation or transmission are shown. Such materials can continue their functionality (i.e., either attenuation or transmission of waves) while keeping a record of extreme events that can cause their transition (i.e., have memory). These metamaterials can be useful in the next generations of advanced and functional acoustic devices.